Risk and severity of motor vehicle crashes in patients with obstructive sleep apnoea/hypopnoea. Issue 6 (30th January 2008) - Mulgrew, A T; Nasvadi, G; Butt, A; Cheema, R; Fox, N; Fleetham, J A; Ryan, C F; Cooper, P; Ayas, N T
Abstract : Background: Obstructive sleep apnoea/hypopnoea (OSAH) appears to be associated with an increased risk of motor vehicle crashes (MVCs). However, its impact on crash patterns, particularly the severity of crashes, has not been well described. A study was undertaken to determine whether OSAH severity influenced crash severity in patients referred for investigation of suspected sleep-disordered breathing. Methods: Objective crash data (including the nature of crashes) for 783 patients with suspected OSAH for the 3 years prior to polysomnography were obtained from provincial insurance records and compared with data for 783 age- and sex-matched controls. The patient group was 71% male with a mean age of 50 years, a mean apnoea-hypopnoea index (AHI) of 22 events/h and a mean Epworth Sleepiness Scale score of 10. Results: There were 375 crashes in the 3-year period, 252 in patients and 123 in controls. Compared with controls, patients with mild, moderate and severe OSAH had an increased rate of MVCs with relative risks of 2.6 (95% CI 1.7 to 3.9), 1.9 (95% CI 1.2 to 2.8) and 2.0 (95% CI 1.4 to 3.0), respectively. Patients with suspected OSAH and normal polysomnography (AHI 0–5) did not have an increased rate of MVC (relative risk 1.5 (95% CI 0.9 to 2.5), p = 0.21). When the impact of OSAH on MVC associated with personal injury was examined, patients with mild, moderate and severe OSAH had a substantially higher rate of MVCs than controls with relative risks of 4.8 (95% CI 1.8 to 12.4), 3.0 (95% CI 1.3 to 7.0) and 4.3 (95% CI 1.8 to 8.9), respectively, whereas patients without OSAH had similar crash rates to controls with a relative risk of 0.6 (95% CI 0.2 to 2.5). Very severe MVCs (head-on collisions or those involving pedestrians or cyclists) were rare, but 80% of these occurred in patients with OSAH (p = 0.06). Conclusion: Patients with OSAH have increased rates of MVCs, and disproportionately increased rates of MVCs are associated with personal injury.